2012
DOI: 10.1021/ie300649d
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer from Single Drops and the Influence of Temperature

Abstract: Temperature can alter the performance of conventional liquid–liquid extraction columns in which one phase is dispersed inside another phase. In this research, the influence of temperature on the extraction process was investigated using a toluene–acetic acid–water chemical system with dominant mass transfer resistance in the organic phase. Single drop experiments with a range of drop size within 2.49–3.77 mm and temperature within 15–40 °C were performed. Results demonstrate significant impact of temperature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Accordingly, the recovery of acetic acid from aqueous solutions has been investigated extensively [1][2][3][4] due to its wide consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the recovery of acetic acid from aqueous solutions has been investigated extensively [1][2][3][4] due to its wide consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In 1973, Dakshinamurty et al [9] just reported the experimental data for this system at temperatures of (303.2, 313.2, and 333.2) K, and in 1985 Badakhshan et al [10] compared experimental data with the predicted values by the universal functional activity coefficient (UNIFAC) model at temperatures of (278.2, 283.2, 293.2, 303.2, and 323.2) K. Considering wide use of this system in liquid-liquid extraction investigations [4,11], the objective of this research is to provide a new series of LLE data for the ternary {water (1) + acetic acid (2) + toluene (3)} system at three specified temperatures of (288.2, 298.2, and 313.2) K. Then NRTL and UNIQUAC models are examined for regression of experimental data and obtaining binary interaction parameters, using Aspen Plus simulator. Also, distribution coefficient and separation factor for acetic acid were determined at different temperatures for the purpose of process design and simulation applications.…”
Section: Introductionmentioning
confidence: 99%
“…As observed in the experiments, drop motion tended to reach a steady value after 50 mm of traveling in the continuous phase. Coincidentally, Saien et al (2012) reported a distance of about 40 mm in the system of toluene-acetic acid-water as adequate to have steady movement. Slater et al (1988) observed a distance of about 30 mm for the chemical system of cumeneacetic acid-water.…”
Section: Setup and Proceduresmentioning
confidence: 98%
“…The droplets at higher temperature tended to have more complex internal turbulence and thus a higher mass transfer rate was achieved. The disturbance can also provide intensification of the Marangoni phenomenon (Saien et al, 2012). Higher mass transfer coefficients can be obtained at higher temperature, but the mutual solubility of phases more or less increases with temperature, which provides a negative impact on subsequent separations.…”
Section: Effect Of Temperature On Mass Transfermentioning
confidence: 99%
See 1 more Smart Citation